Internet of medical things paradigm of wearable devices - Cardona, Manuel; Solanki, Vijender Kumar 1980-; Cena, Cecilia E. García (CRC Press, Taylor & Francis Group, 2021)
1. Fundamentals and Paradigms in the Internet of Things. 2. Internet of Medical Things: Current and Future Trends. 3. An Overview on Wearable Devices for Medical Applications. 4. Blockchain-Based IoT for Personalized Pharmaceuticals. 5. Wearable/Implantable Devices for Monitoring Systems. 6. Werable Sensors for Monitoring Exercise and Fatigue Estimation in Rehabilitation. 7. Conversational Agents for Healthcare Delivery: Potential Solutions to the Challenges of the Pandemic. 8. Role of Big Data in e-Healthcare Application for Managing a Large Amount of Data
Keywords: bisacsh / COMPUTERS / Internet / Security; bisacsh / COMPUTERS / Social Aspects / Human-Computer Interaction